Numerical Simulation and Optimization of Industrial-Scale Fluidized Bed Reactor Coupling Biomass Catalytic Pyrolysis Kinetics - Ruobing Lin; Siyu Wang; Yujie Tao; Xiujuan Feng; Huiyan Zhang (Energies)
The application of fluidized bed reactors to biomass fast pyrolysis is regarded as a promising technology for enabling high-value utilization of biomass. This work established a three-dimensional numerical model of an industrial-scale fluidized bed reactor for biomass catalytic pyrolysis, employing the multiphase particle-in-cell method (MP-PIC) and coupling catalytic pyrolysis kinetics. Primary gas flow rate and biomass–catalyst injection modes were optimized to further improve the performance of the reactor. The model received additional validation from experimental data, primarily to ensure prediction accuracy. The results revealed that an optimal primary gas flow rate of 4 kg/s achieved a peak catalytic efficiency of 71.3%. Using maximum high-quality liquid fuels and adopting a relatively dispersed inlet mode with opposite jetting for biomass and catalyst promoted uniform particle distribution and thermal homogeneity in the dense phase zone, further increasing the catalytic efficiency to 75.6%. With the integration of the multiphase particle-in-cell (MP-PIC) method with catalytic pyrolysis kinetics at the industrial-scale, this work could provide theoretical guidance for designing fluidized bed catalytic pyrolysis reactors and optimizing biomass catalytic pyrolysis processes.